Los 5 pilares del análisis económico del derecho en la era post COVID - Martín Coronado, José Manuel (2023)
This article proposes 5 necessary pillars to do a real Economic Analysis of Law — AED: the legal-economic narrative, the causality diagrams, the mathematical equations, the graphs in Cartesian planes and the use and/or analysis of data. While many lawyers are reluctant to acknowledge the importance of these 5 pillars, economists are divided between those who use them in whole or in part and those who do not. The quantitative approach is at the heart of all economic analysis, and the AED is no exception.